Audit on Venous Thromboembolism (VTE) Assessment in Adult Inpatient Wards on Admission - Syeda Huma Shah (BJPsych Open)
Aims: Aim of this audit was to assess if VTE (Venous thromboembolism) assessments on admission to adult inpatient wards (two working age and one old age ward) at the Inpatient Psychiatry unit are carried out as per the local Trust’s Policy.